The Consequences of Administration Liability Arising from Medical Works - Hussein, Mustafa Rasul (Journal of Legal and Political Studies, 2020)
While administrative responsibility is attained, accordingly there are several impacts will arise as a result , this is including disciplinary or punitive responsibility and compensation resulting from the damages to individuals due to their wrong doing whether it comes from the administration or medical staff working in the public medical facility. As well as it results from the organizational conditions or poor performance or the medical services provided to the beneficiaries people. The legal impact of administrative responsibility which resulted from the medical work can be divided into two parts, the disciplinary responsibility of the employees at the public medical facilities and the management's responsibility for compensation for the patient as a result of the damaged occurred. In order to provide the subject of our study its right and its clarification, clearly we need to address two issues; the first one we need to examine the disciplinary responsibility for workers in the public medical facility, while the second issue is to explain the compensation aspect, and finally we concluded our study with a number of conclusions and recommendations.
Keywords: administrative responsibility; punitive responsibility; damages; disciplinary responsibility; public medical facility